MAP Kinase Phosphorylation and cAMP Assessment in Fungi - Mehrabi, R.; M'Barek, S.B.; Saidi, A.; Abrinbana, M.; De Wit, P.J.G.M.; Kema, G.H.J.
The cyclic AMP (cAMP)signaling and mitogen-activated protein (MAP)kinase pathways are the most important signal transduction pathways in eukaryotes. In many plant pathogenic fungi they play pivotal roles in virulence and development. Identifi cation and understanding the role of signal transduction pathways in regulation of cellular responses require robust biochemical techniques. Determination of both the phosphorylation status of MAPKs and the intracellular levels of cAMP is required to unravel the function of these pathways during adaptation of fungi to environmental stress conditions or when particular fungal genes are disrupted or silenced. Here we describe protocols to determine the phosphorylation status of three different MAPKs including Fus3, Slt2 and Hog1 as well as a protocol to measure the intracellular levels of cAMP levels. These protocols can be adapted for a wide range of fungi.
Keywords: CAMP MEASUREMENT; MITOGEN-ACTIVATED PROTEIN KINASE; PROTEIN KINASE A; PHOSPHORYLATION; FUS3; SLT2; HOG1